Болнички леталитет кај пациенти со акутна бубрежна инсуфициенција во периодот 1990-1994 година - Трајковски, Владимир; Чакалароски, Кочо; Василевска, Кристин (Македонско лекарско друштво, 1999)
The clinical material of patients affected by acute renal failure (ARF) hospitalized in the Department of Nephrology - Skopje, in the period 0.1.01.1990 - 31.12.1994 was used this study. The study is retrospective, descriptive-epidemiological. Hundred and fifteen patients were analyzed and divided in two groups: 27 dead (23.5%) and 88 survived (76.5%). By demographically factors only the older group has a role of a predictor for lethal outcome. It was stated that the duration of the hospitalization has the significance as a factor associated with the condition upon admission of the patient, and better results were reached by the treatment. Out of the etiologic modalities, the medical ARF was distinctive with lethality rate of 25,3%. Main reason for lethal outcome is a cardiogenic shock and heart failure up to 100%. The lethality from surgical reasons is 22,7% and gynecological ARF has 14,3% lethality. A strong positive correlation is established (r=0.93) between multiorgan system failure (MOSF) and lethality. By multivariate analysis, a positiive correlation was established between the lethal outcome and the duration of hospitalization, wound infection and the age of patients. Syndrome of disseminated intravascular coagidation (DIG) affects the lethality. Out of the laboratory parameters the following were found significant: the number of leukocytes, platelets, glycemia and the enzyme GGT. Patients treated with hemodialysis have a significantly higher lethality when compared to the ones treated in conservative manner, which is due to the severiity of the underlying disorder. Undertaking preventive and therapeutic measures to avert the passage from prerenal into intrinsic ARF can be of particular importance for a decrease in the lethality of ARF.
Keywords: acute renal failure (ARF), lethality, outcome